Traditional Chinese Medicine Policies and Development Status in China - WAN Xiaowen, HUANG Rong, MA Lirong, SHI Muran, SHENG Wenbin, ZENG Cheng, WU Ning (Zhongguo quanke yixue)
The research on traditional Chinese medicine policies in China's academic circles became increasingly active and the connotations became richer. However, most of the existing research focused on a certain specific field of traditional Chinese medicine policies, lacking all-round comprehensive research. By systematically retrieving China's traditional Chinese medicine-related policies and journal literature from 2011 to 2023 and obtaining the comprehensive statistical system data of traditional Chinese medicine, this article analyzed Chinese medicine policies from the 12th Five-Year Plan to the 14th Five-Year Plan from the perspectives of Chinese medicine, health care, scientific research, education, industry and culture, reviews relevant Chinese medicine policies and measures, sorts out the development status. It found that China had problems such as insufficient basic Chinese medicine service ability, imperfect Chinese medicine health care network, imperfect education model, and weak scientific research strength. It also proposed to strengthen the traditional Chinese medicine medical system, strengthen health care for treating non-sick patients, strengthen the construction of scientific research forces, integrate and innovate the education model, strengthen the supervision of the traditional Chinese medicine industry, and promote the dissemination of traditional Chinese medicine culture and health education.